(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
In general, topical ophthalmic drug products, especially those used for treating infections, present low effectiveness because of various reasons, from unfavorable drug physicochemical properties to physiological protective mechanisms of the eye. The fact is such group of products holds room for improvement, which could mean the development of better drugs or dosage forms. To achieve this, the knowledge of market composition is essential. The present work studied and compared the antimicrobial ophthalmic markets of Brazil and of the United States (US). Official databank of Brazilian Health Regulatory Agency and of US Food and Drug Administration were assessed for registered antimicrobial topical ophthalmic drug products. Brazilian market has registered greater number of drug products (119) than the US (94), but the latter involves more variety of substances and dosage forms. In both countries, non-innovative products registered as solutions of antibacterials, especially fluoroquinolones and aminoglycosides lead the market. Despite the clinical demand, the US has only one group of antimycotics (polyenes) registered, while in Brazil, there is not any ophthalmic antimycotic product marketed. This study evidences there is not only space for development of newer drugs and formulations but also a demand for already existing technologies and products in both countries.